Effectiveness of reclamation by backfilling and sealing at Kimheden open-pit mine, northern Sweden - Villain, Lucile (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2011)
Reclamation of mine sites is a very recent concept on the scale of mining history. It involves the prevention or mitigation of the environmental impacts from mining, and the establishment of sustainable post-mining uses of the land. Many methods have been tested to reduce the contamination from mining waste, but their actual performance depends highly on the nature of the site. In this thesis, the effectiveness of reclamation is investigated at Kimheden open-pit copper mine in Västerbotten, northern Sweden.Sulphide-containing waste rock left from the extraction of the ore was originally dumped on the surface close to the two open pits at Kimheden. The contact of sulphides with water and oxygen induced the generation of copper- and zinc-rich acid mine drainage. Therefore, reclamation of the mine involved backfilling of the mine waste into the open pits and covering with a till composite dry cover including a sealing layer, in order to reduce the oxygen ingress to the waste.Geochemical and geophysical studies conducted in 2009-2010, complemented by monitoring data from the mining company, were interpreted to assess the success of the reclamation. Long-term annual monitoring of the contaminated drainage by the mining company showed that concentrations of copper and zinc added together have decreased by more than 87% since the completion of reclamation in 1996. However, the decrease occurred rapidly, and metal concentrations in the last ten years have remained stable at values that are still not satisfactory for discharge into the environment. Furthermore, pH in the drainage increased only slightly after reclamation. In 2009, seepage water from one of the pits exhibited a pH of 3.0, and copper, zinc and aluminium concentrations of 3 mg/L, 0.3 mg/L and 20 mg/L, respectively. The partial success of the reclamation in mitigating the acid mine drainage may be explained by persistent oxidation of the backfilled mine waste in spite of the application of the dry cover. This would imply that oxygen gas or oxygenated water ...